2017
DOI: 10.1007/s11368-017-1843-9
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between atrazine and the mineral horizon of soil: a spectroscopic study

Abstract: Purpose In this paper, an attempt was made to explain the long-lasting occurrence of atrazine in soil. Despite the fact that this herbicide has been banned in European Union 10 years ago, it is still detected in the environment. Materials and methods Soil samples (organic and mineral horizon), SiO 2 and Al 2 O 3 sorbents were spiked with atrazine. The ultrasound-assisted extraction coupled with gas chromatography-electron capture detector was performed to establish the atrazine recovery depending on the type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 46 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…The non-adsorption on alumina suggests that in the case of kaolin, which contains both silica and alumina, the adsorption occurs due to the surface groups of silica. This absence of interaction between alumina and atrazine was also observed by Czaplicka et al [36], who simultaneously confirmed through respective FT-IR measurements that the 1,3,5-azidine ring of the atrazine molecule interacts with the SiO 2 molecules, possibly through the formation of hydrogen bonds between atrazine and silica, such as the one shown in Figure S4.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The non-adsorption on alumina suggests that in the case of kaolin, which contains both silica and alumina, the adsorption occurs due to the surface groups of silica. This absence of interaction between alumina and atrazine was also observed by Czaplicka et al [36], who simultaneously confirmed through respective FT-IR measurements that the 1,3,5-azidine ring of the atrazine molecule interacts with the SiO 2 molecules, possibly through the formation of hydrogen bonds between atrazine and silica, such as the one shown in Figure S4.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, the contact between the pollutant and the catalyst surface is necessary. The improvement regarding the removal of atrazine only by the presence of SiO 2 (Figure 2) suggests that the organic molecule can be bonded (through hydrogen bonds) with the Si surface, but not with the Al, as other relevant research has also previously reported [36][37][38].…”
Section: Discussionmentioning
confidence: 55%
“…Namely, although ozone is adsorbed on the surface of the catalyst, promoting the formation of hydroxyl radicals, atrazine molecules are not adsorbed on the catalytic surface, indicating that the mechanism of this organic pollutant's degradation mainly includes its oxidation in the liquid phase. A certain improvement, regarding the removal of atrazine, was only observed in the presence of SiO 2 , suggesting that this organic molecule can bind (probably via weak hydrogen bonds) to the Si surface, but not with the other examined materials/catalysts, as the relevant previous research has also reported [38][39][40].…”
Section: Effect Of Catalysts' Concentrations On the Removal Of Microp...mentioning
confidence: 85%
“…Here, we primarily focus on the interfacial structure and the surface anchoring mechanism of carbaryl on silica using a combination of surface-selective nonlinear vibrational spectroscopy and computational modeling, including molecular dynamics (MD) simulations and ab initio calculations of vibrational spectra. Raman and Fourier transform infrared (FTIR) vibrational spectroscopic methods have been widely applied to study pesticides in bulk solutions and films. , Here, we apply vibrational sum frequency generation (vSFG) spectroscopy, an in situ technique particularly suitable for the analysis of molecules at buried interfaces and sensitive to sub-monolayer amounts of adsorbates. ,, As a coherent nonlinear spectroscopic technique, the vSFG response is highly sensitive to molecular orientation and ordering at the surface, , making vSFG a powerful technique for obtaining detailed chemical information regarding the molecular composition, structure, and interactions of molecules at interfaces. As such, it has become a versatile tool for studies of environmental surfaces and interfaces under ambient conditions ,, and for revealing structure–activity relationships of surface-immobilized compounds, like antimicrobial coatings. …”
Section: Introductionmentioning
confidence: 99%